Lietuvos sienos su Lenkija apsauga 1920−1938 metais - Ereminas, Gintautas (Genocidas ir rezistencija, 2020)
The subject of the article is the protection of the border between the Republic of Lithuania and the Polish-occupied Vilnius region during the politically difficult period of 1920–1938, which was carried out by the Lithuanian People’s Militia, the Lithuanian Riflemen’s Union, the 2nd Marijampolė Regiment, the Frontier Brigade, and the Border Police. On the basis of various documents, an attempt will be made to reconstruct the activities of the units that guarded the border between the Republic of Lithuania and the Polish-occupied Vilnius region in 1920–1938.